Revisiting the useful life computation of Gobindsagar (Bhakra) reservoir. Issue 2 (3rd May 2016) - Koomullil, Deepa S.; Chaube, U.C.; Pandey, Ashish
Abstract : Preserving the existing reservoirs and increasing its useful life is essential for sustainable development. In this context, accurate estimation of sedimentation rate is essential for the realistic determination of useful life of the reservoir. This paper deals with the different approaches used for the computation of sedimentation rate and useful life of Gobindsagar (Bhakra) reservoir, constructed on the river Sutlej in Himachal Pradesh, India. Time-series analysis of the sedimentation rate from a long-term data for the period 1958–2003 obtained from hydrographic survey shows an increasing trend in annual sedimentation. The useful life of Gobindsagar reservoir is also computed after taking into consideration this increasing trend. This investigation also compares the useful life (100% depletion of dead storage) estimated, as per the Project Authority with the useful life computed based on the different approaches analysed in this study. These two estimations are found to be inconsistent. This work revisits the design procedure to resolve this inconsistency and computes the useful life using Brune's step method. It is found that the result obtained from Brune's method is in tune with the useful life calculation based on the actual sedimentation surveys.